ESG ratings impact on cost of capital for Finnish listed companies : Evidence from the Nasdaq Helsinki - Huoponen, Jere (My University, 2026)
The European Union’s ambitious sustainability agenda, tightening corporate social responsibility reporting regulation and the growth of sustainable finance have increased the importance of Environmental, Social and Governance (ESG) attributes in the allocation of both equity and debt capital. The attention given to ESG ratings has divided opinions, as some see it as a way to generate additional value and mitigate risks, whereas others view it as an ideology that compromises capital returns. This confrontation raises an important question for both capital providers and firms: is ESG score associated with the cost of capital? International evidence for this question is somewhat mixed, and Nordics and especially Finland has faced surprisingly low coverage on this topic, despite being one of the global forerunners on sustainability aspects. This thesis addresses the research gap by examining whether ESG scores are associated with the weighted average cost of capital (WACC) and its two components, the cost of equity (COE) and the cost of debt (COD). In particular, the thesis tests whether better ESG performance has had a mitigating impact on these cost of capital variables. The empirical part of the thesis follows a quantitative research design and applies panel data analysis methods for the sample sourced from LSEG Workspace, consisting of 433 firm-year observations from a total of 72 individual companies listed in the Nasdaq Helsinki stock exchange over 2015–2024. The results show no statistically significant relationship between ESG scores and WACC, COE or COD once a set of standard control variables in cost of capital research, as well as firm- and time-level variation are controlled for. The main conclusion is that, in this Finnish sample, with this empirical approach, there is no clear evidence that ESG performance would systematically reduce Finnish publicly quoted firms’ cost of capital. The findings may be associated with a part of the prior European evidence, which suggests that ESG’s ability to reduce cost of capital may depend on the strength of the legislative environment, and that ESG is more relevant in a setting where the jurisdiction and investor protection frameworks are weaker. However, the low explanatory power of the panel regressions indicates that the results should be interpreted as indicative rather than definitive, and alternative research methods and data may be useful in future research to obtain more conclusive evidence.

Euroopan unionin kunnianhimoinen kestävän kehityksen agenda, tiukentuva yrityksiin kohdistuvan kestävyysraportoinnin sääntely ja kestävän rahoituksen kasvu ovat lisänneet ympäristö-, sosiaali- ja hyvän hallintotavan (ESG) merkitystä sekä oman pääoman että vieraan pääoman allokoinnissa. ESG-luokitusten saama huomio on jakanut mielipiteitä, sillä jotkut näkevät sen keinona luoda lisäarvoa ja vähentää riskejä, kun taas toiset näkevät sen ideologiana, joka vaarantaa pääomalle saatavat tuotot. Tämä vastakkainasettelu herättää tärkeän kysymyksen sekä pääoman tarjoajille että yrityksille: onko ESG-pisteytyksellä yhteyttä pääoman kustannukseen? Kansainvälinen tutkimusnäyttö tähän kysymykseen on jokseenkin ristiriitaista, ja Pohjoismaat sekä erityisesti Suomi ovat saaneet yllättävän vähän huomiota tästä aiheesta, vaikka ne ovat kestävän kehityksen edelläkävijöitä globaalisti. Tämä pro gradu -tutkielma käsittelee tutkimusaukkoa tarkastelemalla, ovatko ESG-pisteytykset yhteydessä painotettuun keskimääräiseen pääoman kustannukseen (WACC) sekä sen kahteen osatekijään, oman pääoman kustannukseen (COE) ja vieraan pääoman kustannukseen (COD). Erityisesti tutkielma testaa, onko paremmalla ESG-pisteytyksellä ollut madaltavaa vaikutusta näihin pääomankustannusmuuttujiin. Tutkielman empiirinen osa on toteutettu määrällisellä tutkimusasetelmalla, ja siinä sovelletaan paneeliaineiston analysointimenetelmiä LSEG Workspace -tietokannasta koostetulle otokselle, joka koostuu 433:sta yrityskohtaisesta vuosihavainnoista, kattaen yhteensä 72 Helsingin pörssiin listattua yhtiötä vuosilta 2015–2024. Tulokset eivät osoita tilastollisesti merkitsevää yhteyttä ESG-pisteiden ja WACC:n, COE:n tai COD:n välillä, kun pääoman kustannuksen tutkimuksille tyypilliset kontrollimuuttujat sekä yritys- ja vuositason vaihtelu on otettu huomioon. Pääasiallinen johtopäätös on, että tämän suomalaisen otoksen ja käytetyn empiirisen lähestymistavan pohjalta ei ole selvää näyttöä siitä, että ESG-pisteytys systemaattisesti alentaisi suomalaisten pörssiyhtiöiden pääoman kustannusta. Havainnot ovat yhdistettävissä osaan aiemmasta eurooppalaisesta tutkimusnäytöstä, jonka mukaan ESG:n kyky alentaa pääoman kustannusta saattaa riippua lainsäädäntöympäristön vahvuudesta ja että ESG:n merkitys on relevantimpi maissa, jossa oikeusjärjestelmä ja sijoittajansuoja ovat heikompia. Paneeliregressioiden alhainen selitysaste viittaa kuitenkin siihen, että tuloksia tulisi tulkita suuntaa-antavina eikä lopullisen ratkaisevina, ja että vaihtoehtoiset tutkimusmenetelmät ja -aineistot voivat olla hyödyllisiä tulevissa tutkimuksissa vahvemman tutkimusnäytön saamiseksi.
Keywords: ESG, corporate social responsibility, weighted average cost of capital, cost of equity, cost of debt, panel data